Two new Celtiberian graffiti form Burzau (Borja, Zaragoza) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The paper provides two new celtiberian graffiti from Burzau(Borja, Zaragoza).
Keywords: Celtiberian graffiti; Burzau; Borja (Zaragoza)